CHLORINE STABLE ISOTOPE FRACTIONATION IN EVAPORITES - Eggenkamp H.G.M.; Kreulen R.; van Groos A.F.K. (My University, 1995)
Chlorine isotope fractionation (37Cl/35Cl) between NaCl, KCl, and MgCl2.6H2O and their saturated solutions was determined in laboratory experiments at 22 +/- 2°C. The results are as follows:103 1n α(NaCl--solution) = +0.26 +/- 0.07 (1σ),103 1n α(KCl--solution) = -0.09 +/- 0.09 (1σ),103 1n α(MgCl2.6H2O--solution) = -0.06 +/- 0.10 (1σ),α = - 37Cl/35Cl)precipitate37Cl/35Cl)solution.37Cl of the precipitate decreases systematically during the main phase of halite crystallization but increases again at the latest stage of evaporation. The chlorine isotope fractionation model was tested on a core from the upper Zechstein III salt formation. The salt core contains layers dominated by either halite or K-Mg salts. The K-Mg salts, which are formed during the final stages of evaporation, contain up to 75% carnallite (KMgCl3.6H2O) and bischofite (MgCl2.6H2O). The observed chlorine isotope fractionation in the salt core is in general agreement with the Rayleigh fractionation model. During the main crystallization phase of halite, δ37Cl decreases continuously, but this trend reverses during the final stages when Mg-salts begin to crystallize. It is concluded that δ37Cl can be used as an indicator of evaporation cycles. In addition, it provides quantitative information on the proportion of salt that has been deposited on the input of fresh seawater and on the disturbance by postdepositional processes.